2020
DOI: 10.1002/hep.31222
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Regulates N6‐Methyladenosine RNA Modification in Hepatocarcinogenesis by Inducing RANBP2‐Dependent FTO SUMOylation

Abstract: BaCKgRoUND aND aIMS: Hepatocellular carcinoma (HCC) is associated with high malignancy rates. Recently, a known deacetylase silent information regulator 1 (SIRT1) was discovered in HCC, and its presence is positively correlated with malignancy and metastasis. N 6-methyladenosine (m 6 A) is the most prominent modification, but the exact mechanisms on how SIRT1 regulates m 6 A modification to induce hepatocarcinogenesis remain unclear. appRoaCH aND ReSUltS: Here we demonstrate that SIRT1 exerts an oncogenic role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 39 publications
(83 reference statements)
5
77
0
Order By: Relevance
“…Those genes which were consistently validated in all three HCC cell lines were subject to further studies; h Protein level of LYPD1 was measured in ALKBH5-silenced Huh7 and MHCC97H cells or ALKBH5-overexpressing HCCLM3 cells the growth and invasion of HCC cells via diverse mechanisms [16,17,19]. And two studies have reported ambiguous results about FTO, which may serve as either an oncogene or a tumor suppressor in HCC [21,22]. Meanwhile, our preliminary experiments also found the controversial effects of FTO on proliferation abilities in different HCC cells (Additional file 9: Figure S5a-k).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those genes which were consistently validated in all three HCC cell lines were subject to further studies; h Protein level of LYPD1 was measured in ALKBH5-silenced Huh7 and MHCC97H cells or ALKBH5-overexpressing HCCLM3 cells the growth and invasion of HCC cells via diverse mechanisms [16,17,19]. And two studies have reported ambiguous results about FTO, which may serve as either an oncogene or a tumor suppressor in HCC [21,22]. Meanwhile, our preliminary experiments also found the controversial effects of FTO on proliferation abilities in different HCC cells (Additional file 9: Figure S5a-k).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al illustrate that FTO facilitates the tumorigenesis of HCC via modulating PKM2 demethylation [21]. However, a most recent study delineates that FTO, which is regulated by SIRT1-induced SUMOylation, functions as a tumor suppressor in HCC [22]. These outcomes underscore the complexity of m 6 Amediated effects in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…This, accompanied by an elevated level and redistribution of METTL3 expression in AD hippocampal tissue, likely represents abnormal misfolding and/or aggregation of METTL3, perhaps resembling the frequent aggregation of RNA-binding proteins in neurodegenerative disorders (Arai et al, 2009;Conlon and Manley, 2017). Given that several m6A regulatory proteins are subjected to post-translational ubiquitination and SUMOylation (Zhang et al, 2015;Tai et al, 2017;Du et al, 2018;Zhu et al, 2018;Liu et al, 2020;Xu et al, 2020), it is conceivable that dysregulation of the ubiquitin-proteasome system may contribute to the aggregation of METTL3 in AD (Ihara et al, 2012;Zheng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of METTL14 is associated with tumor differentiation, clinical stage, and microvascular invasion [48]. Low expression of ALKBH5 or FTO predicts an unfavorable marker in lung cancer and HCC [107,108]. IGF2BP2 is considered as a prognostic marker in pancreatic cancer, esophagogastric junction adenocarcinoma and CRC [60,109,110].…”
Section: A Regulators Are Regulated By Ncrnas In Cancermentioning
confidence: 99%